Financial inclusion and micro, small, and medium enterprises (MSMEs) growth in Uganda - Corti Eliab Paul Lakuma; Robert Marty; Fred Muhumuza (Journal of Innovation and Entrepreneurship, 2019)
This paper draws on data from Uganda's 2013 World Bank Enterprise Survey (WBES), which comprises data on 762 firms across Uganda to assess the effects of the business environment, with particular interest on the impact of finance on firm growth by focusing on differences across firm size. Unlike past studies, we use firm level data that allows us to interrogate whether the impact of the business environment is unbiased across firm size. Most importantly, this paper mitigates the risk of the potential measurement error, omitted variable bias, and endogeneity. The results suggest that micro, small, and medium enterprises (MSMEs) in Uganda benefit more from financial access than large firms. These effects are stronger and more sustained among medium firms. The paper interprets these results as evidence that MSMEs are more credit constrained relative to large firms. The paper also discerns that while informality and poor regulatory environment may help divert economic activity from large firms to MSMEs, informality increases the vulnerability of MSMEs to corruption to sustain their informal and invisible status. The policy implication on size, efficiency, and dynamism of the business sector in Uganda is that there is a need to increase not only financial inclusion of MSMEs but also improve the general business environment, particularly the formalization of micro firms.
Keywords: 650; Financial inclusion; Entrepreneurship; Employment; Growth; MSMEs